Commensal colonization reduces Pseudomonas aeruginosa burden and subsequent airway damage - Stoner, Sara N.; Baty, Joshua J.; Novak, Lea; Scoffield, Jessica A. (Frontiers in Cellular and Infection Microbiology, 2023)
Pseudomonas aeruginosa dominates the complex polymicrobial cystic fibrosis (CF) airway and is a leading cause of death in persons with CF. Interestingly, oral streptococcal colonization has been associated with stable CF lung function. The most abundant streptococcal species found in stable patients, Streptococcus salivarius, has been shown to downregulate pro-inflammatory cytokines in multiple colonization models. However, no studies have demonstrated how S. salivarius potentially improves lung function. Our lab previously demonstrated that the P. aeruginosa exopolysaccharide Psl promotes S. salivarius biofilm formation in vitro, suggesting a possible mechanism by which S. salivarius is incorporated into the CF airway microbial community. In this study, we demonstrate that co-infection of rats leads to enhanced S. salivarius colonization and reduced P. aeruginosa colonization. Histological scores for tissue inflammation and damage are lower in dual-infected rats compared to P. aeruginosa infected rats. Additionally, pro-inflammatory cytokines IL-1β, IL-6, CXCL2, and TNF-α are downregulated during co-infection compared to P. aeruginosa single-infection. Lastly, RNA sequencing of cultures grown in synthetic CF sputum revealed that P. aeruginosa glucose metabolism genes are downregulated in the presence of S. salivarius, suggesting a potential alteration in P. aeruginosa fitness during co-culture. Overall, our data support a model in which S. salivarius colonization is promoted during co-infection with P. aeruginosa, whereas P. aeruginosa airway bacterial burden is reduced, leading to an attenuated host inflammatory response.